Adenocarcinoma in the jejunum of a dog: a case report - Hernández, Carlos; Restrepo, Rodrigo (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary A 10-year-old male Pit-bull was attended for presenting sporadic vomiting and occasional diarrhea. In the last 48 hours the patient had presented multiple vomiting and no oral food was tolerated. During the physical examination an abdominal cranial mass was palpated. Survey radiographs of the abdomen and contrast study with barium sulfate suspension showed an accumulation of a radiopaque material causing an intestinal obstruction pattern. During the surgical exploration, the foreign material was extracted from the jejunum using an enterotomy, but an intramural mass was detected occluding the lumen at this point. A complete bowel resection was performed in the intestinal loop affected by the tumor and an end-to-end anastomosis was performed. The histologic examinations revealed an adenocarcinoma involving the entire intestinal wall. The patient recovered from the surgical procedure and no signs of metastasis have been proved nine months after the surgery. Resumen Un perro macho de raza Pitbull de 10 años de edad fue atendido por presentar vómito esporádico en los últimos 2 meses y diarrea ocasional. En las últimas 48 horas el paciente había presentado múltiples vómitos sin tolerar alimentación oral. Al examen clínico se palpó una masa abdominal. Las radiografías abdominales simples y contrastadas con sulfato de bario mostraron un acúmulo de material radiopaco causando un patrón característico de obstrucción intestinal. En la exploración quirúrgica el material causante de la obstrucción que se encontraba en el yeyuno fue retirado mediante enterotomía pero se detectó una masa intraluminal intestinal, por lo que se extrajo el segmento completo y se realizó una enteroanastomosis termino-terminal. El análisis histológico de la masa extraída evidenció un adenocarcinoma envolviendo todo el espesor de la pared intestinal. El paciente se recuperó normalmente y hasta los nueve meses posteriores a la cirugía, no ha aparecido ningún signo de metástasis.